Reproducibility of the peritoneal regression grading score for assessment of response to therapy in peritoneal metastasis. Issue 7 (14th April 2019) - Solass, Wiebke; Sempoux, Christine; Carr, Norman J; Bibeau, Frederic; Neureiter, Daniel; Jäger, Tarkan; Di Caterino, Tina; Brunel, Christophe; Klieser, Eckhard; Fristrup, Claus W; Mortensen, Michael B; Detlefsen, Sönke
Abstract : Aims: The four‐tiered peritoneal regression grading score (PRGS) assesses the response to chemotherapy in peritoneal metastasis (PM). The PRGS is used, for example, to assess the response to pressurised intraperitoneal aerosol chemotherapy (PIPAC). However, the reproducibility of the PRGS is currently unknown. We aimed to evaluate the inter‐ and intraobserver variability of the PRGS. Methods and results: Thirty‐three patients who underwent at least three PIPAC treatments as part of the PIPAC‐OPC1 or PIPAC‐OPC2 clinical trials at Odense University Hospital, Denmark, were included. Prior to each therapy cycle, peritoneal quadrant biopsies were obtained and three haematoxylin and eosin (H&E)‐stained step sections were scanned and uploaded to a pseudonymised web library. For determining interobserver variability, eight pathologists assessed the PRGS for each quadrant biopsy, and Krippendorff's alpha and intraclass correlation coefficients (ICCs) were calculated. For determining intraobserver variability, three pathologists repeated their own assessments and Cohen's kappa and ICCs were calculated. A total of 331 peritoneal biopsies were analysed. Interobserver variability for PRGS of each biopsy and for the mean and maximum PRGS per biopsy set was moderate to good/substantial. The intraobserver variability for PRGS of each biopsy and for the mean and maximum PRGS per biopsy set was good to excellent/almost perfect. Conclusions: Our data support the PRGS as a reproducible and useful tool to assess response to intraperitoneal chemotherapy in PM. Future studies should evaluate the prognostic and predictive role of the PRGS.